2013
DOI: 10.1007/s13593-013-0144-y
|View full text |Cite
|
Sign up to set email alerts
|

Why wheat farmers could reduce chemical inputs: evidence from social, economic, and agronomic analysis

Abstract: Though European policies recommend pesticide reduction, most farmers still manage their crops with a high level of chemical inputs, notably in arable crop-based systems. Factors influencing farmers' practices and the reasons why they do not adopt alternative techniques are not well-known. Actual reports on that topic are based on monodisciplinary analyses either in agronomy, sociology, or economics, whereas farmers' motives are most probably manifold. Therefore, we surveyed winter wheat agricultural practices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 29 publications
3
35
0
Order By: Relevance
“…Surveys have confirmed this trend; awareness of farmers of IPM methods and their usage rises in conjunction with increased farm area. Nave et al [41] described three plant protection strategies that farmers generally apply. In the first strategy, producers restrict the use of plant protection products and at the same time, use practices that reduce pest pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys have confirmed this trend; awareness of farmers of IPM methods and their usage rises in conjunction with increased farm area. Nave et al [41] described three plant protection strategies that farmers generally apply. In the first strategy, producers restrict the use of plant protection products and at the same time, use practices that reduce pest pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Information flow, level of cooperation, and inclusion of a diversity of viewpoints have been shown to influence adoption of environmentally friendly practices as much as economics (Schenk et al 2007). The social capital and involvement of farmers in professional networks can explain engagement in environmental schemes (Mathijs 2003) and adoption of low input practices (Nave et al 2013). A social sciences study (ENDURE 2010b) showed that nearly all farmers moving along the continuum were active members of farmer organizations, whereas isolated farmers were less likely to engage in IPM.…”
Section: Non-technical Factors Of Implementationmentioning
confidence: 99%
“…Low input and organic farming systems have been generally shown to improve environmental sustainability and food safety with potential benefits for health of animals including humans, although a lower and variable productive performance compared with conventional farming systems has been highlighted [3,4]. The use of synthetic fertilizers and agrochemicals within European agricultural systems does not decrease appreciably, although lately the EU policy has implemented a number of recommendations and directives to encourage a drastic reduction of chemical inputs in a sustainability perspective [5]. Fertility management of the soil, particularly the nitrogen (N) availability, is considered the main critical factor limiting both grain yield and protein content in cereal crops.…”
Section: Introductionmentioning
confidence: 99%